Jasper's Basic Mechanisms of the Epilepsies 2012
DOI: 10.1093/med/9780199746545.003.0045
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Homeostasis and GABA Signaling in Temporal Lobe Epilepsy

Abstract: Changes in neuronal chloride homeostasis affect GABA A receptor-mediated transmission and may contribute to epileptic activities. Work on human epileptic tissue suggests that Cl − homeostasis is impaired in some temporal lobe pyramidal cells. GABAergic depolarization of these neurons contributes to rhythmic, interictal events. Intra-neuronal Cl − is controlled in part by two electroneutral cation-chloride cotransporters. NKCC1 mediates Cl − influx, while KCC2 extrudes Cl − thus assuring that GABAergic signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 112 publications
(138 reference statements)
1
57
2
Order By: Relevance
“…Bumetanide inhibits the neuronal chloride cotransporter NKCC1, which acts as a chloride importer. Gamma-aminobutyric acid-mediated excitation has been observed when expression of NKCC1 is higher than expression of the chloride exporter KCC2; e.g., early during development and in the hippocampus of adults with temporal lobe epilepsy [58,59]. Based on the hypothesis that increased expression of NKCC1 may be involved in the development of neuronal hyperexcitability during epileptogenesis in adults, we evaluated whether treatment with bumetanide after pilocarpine-induced SE alters the long-term consequences of the brain insult [60].…”
Section: Examples For Synergistic Drug Combinationsmentioning
confidence: 99%
“…Bumetanide inhibits the neuronal chloride cotransporter NKCC1, which acts as a chloride importer. Gamma-aminobutyric acid-mediated excitation has been observed when expression of NKCC1 is higher than expression of the chloride exporter KCC2; e.g., early during development and in the hippocampus of adults with temporal lobe epilepsy [58,59]. Based on the hypothesis that increased expression of NKCC1 may be involved in the development of neuronal hyperexcitability during epileptogenesis in adults, we evaluated whether treatment with bumetanide after pilocarpine-induced SE alters the long-term consequences of the brain insult [60].…”
Section: Examples For Synergistic Drug Combinationsmentioning
confidence: 99%
“…It may revert excitation mediated by GABA through modifying chloride homeostasis. It suppresses GABA-generated network activities that contribute to the rhythmic interictal events (14,15). Interictal events were not detected in the current case after bumetanide treatment.…”
Section: Discussionmentioning
confidence: 61%
“…This difference can be explained by experimental differences since Zhu et al [44] used slices that presumably expressed half of the KCC2 protein content as compared to wild-type animals [44], whereas in our study, we employed slices from normal rats with normal expression of KCC2. Underexpression of KCC2 can in fact result in Cl − homeostasis changes leading to a switch in GABA A receptor signaling from hyperpolarizing to depolarizing [19,26]. Experimental data have also shown that epileptiform activity induced by 4AP leads to downregulation of KCC2 expression [8,31].…”
Section: Modulation Of Short-and Long-lasting Events By Blocking Kcc2mentioning
confidence: 99%